INVESTIGATING TEACHERS’ STRATEGIES TO PROMOTE LEARNER AUTONOMY IN ENGLISH LANGUAGE TEACHING (ELT) PRACTICE - Anisatul Karimah (Getsempena English Education Journal, 2020)
More and more educational stakeholders are now concerned on learner autonomy (later will be abbreviated as LA) as a fundamental key to actualize an effective and successful instructional process. While research addressing strategies to promote LA has been conducted in ample amount, this research tries to include a more holistic coverage. This research aims at investigating strategies or activities that teachers implement in English language classroom in fostering LA, what reasons are behind the selection of those activities, and to what extent those activities enable LA to take place. Data were collected from 35 teacher respondents who have taught junior high school or higher levels. Questionnaire and semi-guided interview were employed to yield relevant data. Findings show that activities related to psychological dimension become the most favoured ones to apply in the classroom. It is followed by social, technical, and political dimensions accordingly. Those activities are applicable to certain situations and extent.